Scientists as News Sources in the Aftermath of Disasters : Trends in News Coverage Following Two Devastating Tsunamis - Buelow, Ellen K.; Her, Xai (My University, 2013)
Natural disasters are becoming more frequent in the United States (NCDC, 2013), and this increase will result in more people being affected. To mitigate the loss of life, it is important that as many people as possible understand the language of disasters, a language based on scientific terms. Unfortunately, Americans struggle to understand scientific concepts and terminology. Outside of formal education settings, most Americans learn about science through media sources (Soroka 2002; Nisbet and Kotcher 2009). The media relies on scientists to searve as expert sources of information. Prior to December, 2004, the media frequently used the colloquial and inaccurate term, 'tidal wave' to describe tsunamis. However, in the aftermath of the 2004 Indian Ocean Tsunami, the media shifted from the inaccurate term to the scientifically correct term, 'tsunami'. Comparing trends in the 2004 tsunami data to the ongoing analysis of the 2011 tsunami, the purpose of this study was to test the hypothesis that there has been a shift in the information sought from scientists, due to the massive coverage of the 2004 tsunami, which increased the tsunami-related knowledge of the media and the general public.
Color poster with text, graphs, and charts.
Keywords: Terminology--Natural distasters; Scientists--Influence of; Media coverage--Natural disasters; Posters